Glucosinolates 2016
DOI: 10.1007/978-3-319-26479-0_16-1
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Glucosinolates in Broccoli

Abstract: Broccoli is a rich source of health-promoting antioxidants and anticarcinogenic glucosinolates, which has long been recognized for their outstanding benefits to human nutrition and plant defense. The composition and content of glucosinolate are closely associated with the flavor and anticancer activity of broccoli. Up to now, broccoli is among a few Brassica vegetables, in which the biosynthetic pathway of glucosinolate has been widely studied and has attracted extensive attention. Recent studies in glucosinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 211 publications
(185 reference statements)
0
4
0
Order By: Relevance
“…High standard deviation (SD) was observed in the samples of Beneforte® broccoli, a variety reported to have high GRA content (Traka et al ., 2013). Most of the samples ranged between 200 and 600 mg/100 g DW, where similar GRA content was reported by other authors (Miao et al ., 2017; Li et al ., 2021). The second most dominant GSL was GB with a range of 10–540 mg/100 g DW and a mean of 189 ± 116 mg/100 g DW.…”
Section: Resultsmentioning
confidence: 99%
“…High standard deviation (SD) was observed in the samples of Beneforte® broccoli, a variety reported to have high GRA content (Traka et al ., 2013). Most of the samples ranged between 200 and 600 mg/100 g DW, where similar GRA content was reported by other authors (Miao et al ., 2017; Li et al ., 2021). The second most dominant GSL was GB with a range of 10–540 mg/100 g DW and a mean of 189 ± 116 mg/100 g DW.…”
Section: Resultsmentioning
confidence: 99%
“…Several biological activities, such as antioxidants, antimicrobials, anti-proliferative, antiviral, and anti-inflammatory agents have been attributed to glucosinolates and their hydrolysis products ( Heldt and Piechulla, 2011 ). Glucosinolates are secondary metabolites naturally produced in response to biotic stress in Brassicaceae plants ( Miao et al, 2017 ). The biological activity of glucosinolates is mainly dependent on their class or origin and conditions of their hydrolysis ( Griffiths et al, 1998 ; Aires et al, 2009a ).…”
Section: Antimicrobial Activity Of Glucosinolates and Their Hydrolysi...mentioning
confidence: 99%
“…Afterwards, SFN extraction was performed by utilizing dichloromethane at room temperature and reconstituting the concentrated extracts in acetone prior to determination of the SFN content [155,156]. In some cases, it has been reported that a step prior to hydrolysis is added where glucoraphane is isolated and incubated with 2-(N-morpholino) ethanesulfonic instead of acidic water [148,158]. In a recent study, SFN isolation (from broccoli) was attempted by solid-phase extraction, with the aim to examine the different factors that can potentially affect the extraction process [139].…”
Section: Extraction Of Sulforaphanementioning
confidence: 99%